2015
DOI: 10.5897/jmld2015.0099
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of occult hepatitis B virus (HBV) infections in haemodialysis patients in Khartoum State, Sudan from 2012 to 2014

Abstract: This study was carried out to detect occult hepatitis B virus (OHB) among haemodylsis patient inKhartoum State, Sudan. Antigen capture enzyme linked immunosorbent assay (ELISA) to detect hepatitis B surface antigen (HBsAg), competitive ELISA to detect Hepatitis B core antibody (HBcAb) antibodies and polymerase chain reaction (PCR) to detect hepatitis B virus (HBV) DNA were used to analyze 100 plasma samples collected from patients in 3 hospitals (El Amel Hospital, Bashair Hospital and Salma Hospital) during th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
1

Year Published

2016
2016
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 19 publications
0
2
1
Order By: Relevance
“…This prevalence is in agreement with the results in the literature, among haemodilysis patients that range between 0 to 58% in countries such as Canada, Turkey, Italy, Spain, Iran, Brazil and Egypt [5,7,18,19] and it is also in agreement with the findings studies conducted in Khartoum State, (1), West kordofan State, Sudan [2] and in El Gazeera State, Sudan [20] in which the frequencies of OHB among haemodialysis patients was 3.3%, 17.5% and 11.5%, respectively but disagrees with studies from Sudan in which no OHB was detected among haemodialysis and blood donors patients respectively [6,15] and a study from Iran in which no OBH cases were found among haemodialysis patients. Although, the results of the present study and other studies [1,2,20,21]; highly supported the existence of OHB in hemodialysis patients, more studies are needed to fully elucidate the incidence of OHB in Sudan [22,23]. The conflicts in the reported incidences of occult HBV infection among several studies, including this study, could be attributed to several factors such as the sensitivity of the various molecular biology techniques used in detection of HBV DNA, the prevalence of HBV in geographical area, the storage of the sample, the age and sex of patients and the differences in the studies sample size [14,24,25].…”
Section: Discussioncontrasting
confidence: 54%
See 1 more Smart Citation
“…This prevalence is in agreement with the results in the literature, among haemodilysis patients that range between 0 to 58% in countries such as Canada, Turkey, Italy, Spain, Iran, Brazil and Egypt [5,7,18,19] and it is also in agreement with the findings studies conducted in Khartoum State, (1), West kordofan State, Sudan [2] and in El Gazeera State, Sudan [20] in which the frequencies of OHB among haemodialysis patients was 3.3%, 17.5% and 11.5%, respectively but disagrees with studies from Sudan in which no OHB was detected among haemodialysis and blood donors patients respectively [6,15] and a study from Iran in which no OBH cases were found among haemodialysis patients. Although, the results of the present study and other studies [1,2,20,21]; highly supported the existence of OHB in hemodialysis patients, more studies are needed to fully elucidate the incidence of OHB in Sudan [22,23]. The conflicts in the reported incidences of occult HBV infection among several studies, including this study, could be attributed to several factors such as the sensitivity of the various molecular biology techniques used in detection of HBV DNA, the prevalence of HBV in geographical area, the storage of the sample, the age and sex of patients and the differences in the studies sample size [14,24,25].…”
Section: Discussioncontrasting
confidence: 54%
“…Hepatitis B virus (HBV) is a species of the genus Orthohepadnavirus, which belongs to the family of Hepadnaviridae virus [1]. HBV is highly contagious, and is considered as the most commonly transmitted blood borne virus in the health care setting worldwide.…”
Section: Introductionmentioning
confidence: 99%
“…For example, Honarkar et al found a 22% prevalence of positive HBV DNA in seronegative chronic liver patients in IR Iran ( 63 ). Another study from Sudan on 91 HBsAg negative patients revealed that 51.6% of them had positive HBc antibodies and 3.3% had HBV DNA using PCR ( 64 ). Carcinogenicity is not limited only to occult HBV patients.…”
Section: Discussionmentioning
confidence: 99%